The Influence of Director Expertise and Executive Expertise on Firm Performance (An Empirical Study of the Two-tier Board System in Indonesia) - Adri Putra Nugraha (AIBPM Publisher, 2023)
This research aimed to assess the influence of the expertise of boards of directors and executives on manufacturing companies' performances in Indonesia. The independent variable set was Director and Executive Expertise measured by the proportion of board members who have academic degrees (graduate and postgraduate) and professional certifications in business and finance, while the dependent variable was Firm Performance measured by Return on Assets, Return on Equity, and Tobin's Q. The objects of research were manufacturing companies in Indonesia, whose data were obtained from the website of the Indonesia Stock Exchange in 2014-2018. Separate regression analysis of data was performed for each group of board members. The study found that academic degrees and professional certifications in business or finance held by directors and executives did not affect Firm Performance across all proxies because, among others, most companies in Indonesia were family-owned. As the implications, companies can consider Director Expertise as a necessary thing for improving their performances. Members of boards who have more relevant expertise, experiences, knowledge, and skills can develop decision-making and drive more strategy in making more decisions to solve problems and improve their firms' performances.